Papa's mechanical fish - Fleming, Candace; Kulikov, Boris, 1966- (New York : Farrar Straus Giroux, 2013)
In the summer of 1851, with encouragement and ideas provided by his family, an inventor builds a working submarine and takes his family for a ride. Includes notes about Lodner Phillips, the real inventor on whom the story is based.
"Margaret Ferguson books."
Includes bibliographical references.
AD 480
Accelerated Reader
Keywords: Phillips, L. D. -- 1825-1869 -- Juvenile fiction; Inventors -- Juvenile fiction; Families -- Juvenile fiction; Submarines (Ships) -- Juvenile fiction; Historical fiction -- Juvenile literature; Biographical fiction -- Juvenile literature